Considering the Influence of Coronary Motion on Artery-Specific Biomechanics Using Fluid–Structure Interaction Simulation - Nicholas A. T. Fogell; Miten Patel; Pan Yang; Roosje M. Ruis; David B. Garcia; Jarka Naser; Fotios Savvopoulos; Clint Davies Taylor; Anouk L. Post; Ryan M. Pedrigi; Ranil de Silva; Rob Krams (Annals of Biomedical Engineering, 2023)
The endothelium in the coronary arteries is subject to wall shear stress and vessel wall strain, which influences the biology of the arterial wall. This study presents vessel-specific fluid–structure interaction (FSI) models of three coronary arteries, using directly measured experimental geometries and boundary conditions. FSI models are used to provide a more physiologically complete representation of vessel biomechanics, and have been extended to include coronary bending to investigate its effect on shear and strain. FSI both without- and with-bending resulted in significant changes in all computed shear stress metrics compared to CFD ( p = 0.0001). Inclusion of bending within the FSI model produced highly significant changes in Time Averaged Wall Shear Stress (TAWSS) + 9.8% LAD, + 8.8% LCx, − 2.0% RCA; Oscillatory Shear Index (OSI) + 208% LAD, 0% LCx, + 2600% RCA; and transverse wall Shear Stress (tSS) + 180% LAD, + 150% LCx and + 200% RCA (all p